Living Together: Discourses on Citizenship in Turkey - Öztürk, Armagan; Satici, Murat (Nomos Verlagsgesellschaft mbH & Co. KG, 2019)
The contemporary grounds for the critique of modern politics have also populated debates on today’s questions of democracy, political participation, the public sphere, pluralism, gender, ecology and freedom, to name but a few. It should not be forgotten that the problems of living together necessitate overcoming the misperception of politics as only an act between individuals, nations, institutions and political ideologies. Indeed, the problem of living together is a matter of living with others, with the state and its institutions, animals and nature, art and cultures. This political dimension is also manifest in every element of practical life, thus making it necessary to take into consideration gender, disability rights, nature and ecology, animals, social media, and cultural, computational and artistic freedom issues in the practice and politics of living together. Therefore, living together does not signify merely the inter-human sphere. Therefore, this book contains 13 chapters focusing on various dimensions of living together.